2000
DOI: 10.1007/s002620000113
|View full text |Cite
|
Sign up to set email alerts
|

Development of a new vaccine formulation that enhances the immunogenicity of tumor-associated antigen CaMBr1

Abstract: Aberrant glycosylation is one of the most constant traits of malignant cells. The CaMBr1 hexasaccharide antigen, originally defined on the human breast carcinoma cell line MCF7, is expressed on some normal tissues but overexpressed in a high percentage of human breast, ovary, prostate and lung carcinomas. CaMBr1 overexpression is associated with poor prognosis. The epitope consists of the tetrasaccharide Fuc(alpha1-2)Ga1(beta1-3)GalNAc(beta1-3)Ga1alpha-O-spacer, which has recently become available as a synthet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Mouse studies have confirmed the generation of antibodies against globo H after vaccination with KLH or CRM197 (diptheria toxoid) conjugates, prepared by a direct conjugation protocol (18,19). There was evidence of a polyclonal antibody response, mediation of complement cytotoxicity, and binding of IgM antibodies with MCF-7 breast cancer cells (18).…”
Section: Immunization Of Metastatic Breast Cancer Patients With a Fulmentioning
confidence: 74%
“…Mouse studies have confirmed the generation of antibodies against globo H after vaccination with KLH or CRM197 (diptheria toxoid) conjugates, prepared by a direct conjugation protocol (18,19). There was evidence of a polyclonal antibody response, mediation of complement cytotoxicity, and binding of IgM antibodies with MCF-7 breast cancer cells (18).…”
Section: Immunization Of Metastatic Breast Cancer Patients With a Fulmentioning
confidence: 74%
“…[17] We decided to use quite a long spacer (adipic acid) between the saccharide moiety and the protein, in order to leave the sugar epitope exposed on the protein surface. The presence of the allyl group at the anomeric position permitted its manipulation in order to provide an anomeric linker for the conjugation.…”
Section: Resultsmentioning
confidence: 99%
“…The complete immunogenic evaluation is described in detail elsewhere. [17] In summary, the tetrasaccharide moiety was recognized by the Mab MBr1 in a dose-dependent manner with both conjugates. Such result indicates that the conjugation process neither compromises proper presentation of the epitope, nor modifies its conformation.…”
Section: Resultsmentioning
confidence: 99%
“…60 Globo H has therefore become one of the most attractive carbohydrate-based targets for cancer vaccine development. [61][62][63] Previous epitope mapping studies of the anti-Globo H mAb MBr1 indicated that the terminal tetrasaccharide (residue CDEF) is the minimal antigenic structure for Globo H recognition; 64,65 the structural rigidity is crucial for MBr1 binding. 66,67 The pursuit of higher Ag epitope specicity encouraged us to develop a chemically well-dened immunogenic glycoconjugate that carries Globo H hexasaccharide glycan with the specic aim of generating highly specic Abs that can bind to Globo H antigens on tumor cells.…”
Section: Introductionmentioning
confidence: 99%